PRACTICES AFFECTING REPRODUCTION (PAR) SCORE OF DAIRY FARMERS IN WESTERN REGION OF PUNJAB - KASRIJA, RAJESH; VERMA, HARISH KUMAR (The Indian Journal of Animal Reproduction, 2023)
A study was conducted in the western region of Punjab to know the awareness level of dairy farmers possessing small (1-9 animals), medium (10-30 animals) and large (more than 30 animals) dairy units about the practices affecting reproduction (PAR). There was significant difference in observed PAR knowledge score of small, medium and large dairy farmers. Majority of the dairy farmers had medium PAR awareness level, which was found to be highly positively correlated with age and land holding of farmers. The study describe dire need of strong extension agencies for knowledge dissemination and highlightens separate strategies to be undertaken for improving the PAR awareness level of farmers operating different dairy units for profitability and sustainability.